Life-Cycle Effects on Corporate Returns on Retentions - Grabowski, Henry G.; Mueller, Dennis C. (The Review of Economics and Statistics, 1975)
IN a recent paper investigating the efficiency of earnings retentions, Baumol, Heim, Malkiel and Quandt (1970) (hereafter BHMQ) estimate the rate of return on earnings retentions, debt and new equity for a large cross section of firms. They find new equity earns considerably higher returns than the ploughback of profit and depreciation, with the returns on new debt falling between. BHMQ do not explain these striking results, beyond suggesting a lack of market discipline on the reinvestment of internal funds. In their concluding remarks, they pose a number of open questions for future research and analysis